Of Gold, Spanish Conquistadors, And Ibaloi Generational Memory - Dela Paz, Ferdinand Isidro (Hukay; Vol 18)
Michael Armand P. Canilao 2011. Baguio City:  Cordillera Studies Center, University of the Philippines, Baguio